Respuesta :
So i will show you how to do this step by step. :)
So first thing you need to know, what ever you do to one side, you must do to the other.
And we will be using the rules of PEMDAS.
P - parentheses
E - exponents
M - multiplication
D - division
A - addition
S - subtraction
So now that we got that out of the way lets solve our equation.
Now Pemdas says we have to solve Parentheses first before anything else.
So lets multiply the -3 to both of the variables and numbers within the parentheses...
-3(x + 3) = -3(x + 1) -5
So you would multiply -3 times x which is just -3x :)
and -3 times -3 which is 9
And for the second equation...
multiply -3 times x which = -3x
and -3 times 1 equals -3
So lets set up our new equation..
-3x - 9 = -3x -3 - 5
Now since there are no other steps we could possible do with "EMDA"
We can skip all the way to subtraction.
So just subtract -3 - 5 = -8
So lets set up our equation again...
-3x - 9 = -3x - 8
Now we have to isolate the x's to be alone..
So lets add +9 to both sides to cancel out on the left side and add to 8 on the right hand side of our equation.
-3x - 9 = -3x - 8
+9 = + 9
the nines on the left side disappear and we solve on the right side.
-3x = -3x +1
Now we can add +3x from the right side to the left to try to put our x's together.
soooo..
-3x = -3x + 1
+3x = +3x
WAIT. WAIT. WAIT. -3x + 3x = 0
So what is going on?
Well set what we have left
0 = 1
That looks like we simplified it the most we can and x isnt even in the answer!! So this means there is NO SOLUTION.
Yes thats right after all your hard work trying to figure out X, there actually is no answer...
SO, Answer is NO SOLUTION!
Good Luck! :P
So first thing you need to know, what ever you do to one side, you must do to the other.
And we will be using the rules of PEMDAS.
P - parentheses
E - exponents
M - multiplication
D - division
A - addition
S - subtraction
So now that we got that out of the way lets solve our equation.
Now Pemdas says we have to solve Parentheses first before anything else.
So lets multiply the -3 to both of the variables and numbers within the parentheses...
-3(x + 3) = -3(x + 1) -5
So you would multiply -3 times x which is just -3x :)
and -3 times -3 which is 9
And for the second equation...
multiply -3 times x which = -3x
and -3 times 1 equals -3
So lets set up our new equation..
-3x - 9 = -3x -3 - 5
Now since there are no other steps we could possible do with "EMDA"
We can skip all the way to subtraction.
So just subtract -3 - 5 = -8
So lets set up our equation again...
-3x - 9 = -3x - 8
Now we have to isolate the x's to be alone..
So lets add +9 to both sides to cancel out on the left side and add to 8 on the right hand side of our equation.
-3x - 9 = -3x - 8
+9 = + 9
the nines on the left side disappear and we solve on the right side.
-3x = -3x +1
Now we can add +3x from the right side to the left to try to put our x's together.
soooo..
-3x = -3x + 1
+3x = +3x
WAIT. WAIT. WAIT. -3x + 3x = 0
So what is going on?
Well set what we have left
0 = 1
That looks like we simplified it the most we can and x isnt even in the answer!! So this means there is NO SOLUTION.
Yes thats right after all your hard work trying to figure out X, there actually is no answer...
SO, Answer is NO SOLUTION!
Good Luck! :P
Answer: No solution
Step-by-step explanation:
The given equation: [tex]-3(x + 3) = -3(x + 1) - 5[/tex]
Using BODMAS (Bracket , of , Divide , Multiply, Add, Subtract), we have
[tex]-3x -9 = -3x-3- 5[/tex]
Add 3x and 9 on both sides , we get
[tex]\\\\\Rightarrow\ -3x+3x=9-8\\\\\Rightarrow\ 0=1[/tex]
Which is not possible .
Therefore, the given equation has no solution.